Gramática histórica del español para francófonos universitarios de nivel C1: en torno a una propuesta didáctica - Fernández Martín, Patricia (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
Through a didactic expe-rience of teaching Spanish histori-cal grammar to a group of C1-level francophone students in Madrid, the aim of this paper is to demon-strate that the flexibility of the task-based approach lets teachers suc-cessfully combine the institutional requirements with the needs of the students. For this, the theoretical foundations are exposed (concept of tasks, inductive teaching of grammar), as well as the research methodology (creation of teaching material, session to session de-scription) and the results achieved (complexity of the contents, motiva-tion to learn it from a different way). The main conclusion points out that it can be highly effective for learners to turn the assessment tools required by planning into ena-bling and final tasks achievable by the students
Keywords: Historical Grammar; Spanish as a Foreign Language; Francophones; ask-based Approach; Task-based Approach; nductive Grammar Teaching